Foster Fathers: their experiences and contributions to fostering - Wilson, Kate; Fyson, Rachel; Newstone, Simon (Blackwell Publishing, 2007)
The paper reports some of the findings of an exploratory study which looks at foster fathers’ experiences of fostering and discusses their routes into foster care and their perspectives on their roles and tasks. The study collected quantitative and qualitative data by approaching all foster fathers registered with a single independent fostering agency based in southeast England. They were asked about their personal and professional attributes, and their experiences of and views concerning the role of foster father. The study discusses the foster fathers’ motivation to foster, and argues that what they see as its positives and drawbacks, and how it fits into their own family lives, are all relevant to improving service recruitment, delivery and retention. The study produced some evidence about the distinctive and positive contribution which foster fathers see themselves making to the lives of the children they foster. Further research is needed to refine our knowledge of what this contribution may be. Such knowledge could potentially develop our understanding of the roles of fathers in child development more generally as well as fine-tuning practice in matching what particular placements have to offer to the needs of individual children.